Description of a new unusual Pselaphodes Westwood, 1870 (Coleoptera: Staphylinidae: Pselaphinae) from Nepal - Bekchiev, Rostislav; Hlaváč, Peter (Zootaxa, 2013)
A recent work of Yin et al. 2013 provides a description of an interesting species Pselaphodes monoceros Yin & Hlaváč, 2013. This species was tentatively placed in the genus Pselaphodes Westwood, 1870 although it displays some characters atypical for the genus, such as nearly symmetrical maxillary palpi, with palpomere III without distinct lateral projection and male sexual character located on the clypeus. On the basis of this species the taxonomical limit of the genus was extended, but the correctness of this placement will have to be confirmed by serious phylogenetic analysis (Yin et al. 2013).